An overview of geophysical technologies appropriate for characterization and monitoring at fractured-rock sites. (15th December 2017) - Day-Lewis, Frederick D.; Slater, Lee D.; Robinson, Judy; Johnson, Carole D.; Terry, Neil; Werkema, Dale
Abstract: Geophysical methods are used increasingly for characterization and monitoring at remediation sites in fractured-rock aquifers. The complex heterogeneity of fractured rock poses enormous challenges to groundwater remediation professionals, and new methods are needed to cost-effectively infer fracture and fracture-zone locations, orientations and properties, and to develop conceptual site models for flow and transport. Despite the potential of geophysical methods to "see" between boreholes, two issues have impeded the adoption of geophysical methods by remediation professionals. First, geophysical results are commonly only indirectly related to the properties of interest (e.g., permeability) to remediation professionals, and qualitative or quantitative interpretation is required to convert geophysical results to hydrogeologic information. Additional demonstration/evaluation projects are needed in the site remediation literature to fully transfer geophysical methods from research to practice. Second, geophysical methods are commonly viewed as inherently risky by remediation professionals. Although it is widely understood that a given method may or may not work at a particular site, the reasons are not always clear to end users of geophysical products. Synthetic modeling tools are used in research to assess the potential of a particular method to successfully image a target, but these tools are not widely used in industry. Here, we seek to advance the application of geophysical methods to solve problems facing remediation professionals with respect to fractured-rock aquifers. To this end, we (1) provide an overview of geophysical methods applied to characterization and monitoring of fractured-rock aquifers; (2) review case studies showcasing different geophysical methods; and (3) discuss best practices for method selection and rejection based on synthetic modeling and decision support tools. Highlights: Geophysical methods can improve characterization and monitoring in fractured rock. Integration of multiple data types is critical to develop site conceptual models. Technology transfer is needed to accelerate adoption of geophysical methods. Synthetic modeling supports go/no-go decisions for the use of geophysics.